De la complexité d’enseigner une histoire biblique laïque - Daniel Faivre (Cahiers d’histoire)
Reducing religious fundamentalism presupposes a secular and neutral teaching of the founding texts which support them, the Bible in particular. But the historical "truths" it contains are today reassessed by archaeologists as well as historians and even theologians. However, their dissemination within the framework of a school of the Republic poses the vast question of the training of teachers, largely neglected in France for more than a century, on this part of ancient history.